Impact of Next-Generation Mobile Technologies on Early Childhood Education: Educator Adaptation and Child Development - Adeoye, Moses Adeleke (Southeast Asia Early Childhood Journal, 2025)
Integrating next-generation mobile technologies in early childhood education is an area of significant interest, particularly in developing countries like Nigeria, where socio-economic and infrastructural challenges influence educational practices. This research explores the impact of mobile technologies on early childhood learning, focusing on their potential to enhance engagement, facilitate communication, and support educators. Employing a qualitative research design, the study gathered data through interviews and focus groups involving educators, parents, and child development experts. This approach provided comprehensive insights into the experiences and perspectives of stakeholders regarding mobile technology integration in educational settings. The findings reveal that mobile technologies can significantly enhance children’s engagement and learning outcomes; however, challenges such as unequal access to devices, insufficient educator training, and gaps in parental involvement persist. Stakeholders expressed a need for targeted professional development and improved communication strategies to maximise the benefits of mobile technologies in early childhood education. In conclusion, this research underscores the urgency of addressing these challenges to leverage the potential of mobile technologies for young learners. The contributions of this study extend to providing practical recommendations for educators and policymakers, thereby informing strategies for effective technology integration. Ultimately, this research fills a critical gap in the literature by offering insights specific to the Nigerian context while contributing to the broader discourse on technology use in global early childhood education.